Advanced Photonic Processes for Photovoltaic and Energy Storage Systems. Issue 39 (24th August 2017) - Sygletou, Maria; Petridis, Constantinos; Kymakis, Emmanuel; Stratakis, Emmanuel
Abstract: Solar‐energy harvesting through photovoltaic (PV) conversion is the most promising technology for long‐term renewable energy production. At the same time, significant progress has been made in the development of energy‐storage (ES) systems, which are essential components within the cycle of energy generation, transmission, and usage. Toward commercial applications, the enhancement of the performance and competitiveness of PV and ES systems requires the adoption of precise, but simple and low‐cost manufacturing solutions, compatible with large‐scale and high‐throughput production lines. Photonic processes enable cost‐efficient, noncontact, highly precise, and selective engineering of materials via photothermal, photochemical, or photophysical routes. Laser‐based processes, in particular, provide access to a plethora of processing parameters that can be tuned with a remarkably high degree of precision to enable innovative processing routes that cannot be attained by conventional approaches. The focus here is on the application of advanced light‐driven approaches for the fabrication, as well as the synthesis, of materials and components relevant to PV and ES systems. Besides presenting recent advances on recent achievements, the existing limitations are outlined and future possibilities and emerging prospects discussed. Abstract : The enhancement of the performance and competitiveness of photovoltaic (PV) and energy‐storage (ES) systems requires the adoption of precise, but simple and low‐cost manufacturing solutions, compatible with large‐scale and high‐throughput production lines. The application of advanced light‐driven approaches for the fabrication and synthesis of materials and components relevant to PV and ES systems are reviewed.